Model of employees’ readiness to change: two steps CB SEM analysis - Mardhatillah, Amy Mardhatillah; Abdul Rahman, Shukran; Ismail, Khamsiah (2016)
This study investigates model of employees’ readiness to change based on the psychosocial predictors namely; appropriateness of change, management support, change efficacy, individual spirituality and openness to experience. The present study also examined the role of job satisfaction and organizational commitment in mediating the relationship between psychosocial predictor and employee readiness to change.428 random sampling of a Higher Learning Institution in Malaysia consisting 214 academic staff and 214 non academic staff were participated in this study. Two steps CB SEM analysis was used to answer the research questions. CFA result indicated that all measurement used are valid. The structural model in the present study indicates goodness-of-fit with RMSEA less than 0.08 and CFI, AGFI and GFI ranged between 0.063-0.888. The competing model was run to find a better model fitting. Competing model three indicates that management support and individual change efficacy significantly predicted employees’ readiness to change, while openness to experience and appropriateness of change predicted employees’ readiness to change via intervening variables namely job satisfaction and organizational commitment. Individual spirituality indirectly predicted employees’ readiness via openness to experience. Findings in this study can be used to enhance employee readiness as well as a general framework in preparing intervention for enhancing employee readiness to change.